Risk management of metabolic disorders in the use of antipsychotics - G. E. Mazo; A. O. Kibitov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Cardio-metabolic risk factors and diabetes mellitus type 2 are highly prevalent in patients with schizophrenia. Decrease of metabolic risks associated with use of atypical antipsychotics is connected with the development of specialised programs. They can prevent and treat metabolic disorders. This article presents a comprehensive approach to the problem and proposes a solution to minimise the risk of metabolic disorders. The analysis dependence risk of formation of metabolic disorders with genetic factors, behavioral disorders, associated with schizophreniaand therapypresented in the article.